Agent-based asynchronous training in distributed software development. (2nd June 2020) - Ray, D. Manoj; Samuel, Philip
In the changing software development, training on tools and techniques are necessary for the developers for better quality. Global software development faces great challenge for employee training as project members are scattered geographically. Developers should aware of the custom and culture of co-developers to improve their social and interpersonal competencies such as negotiation, teamwork, conflict resolution, time management, leadership, and communication using common language. The paper discussed a framework for agent based training model that can simulate global software development from different cultures; allows learners to train asynchronously as the agents are always available, and permits to play different roles in the various stages of project development. The framework also provides effective client training on product and effective for the discussion between the client and the developer and thus reduces the effort. The model was evaluated with online geographically separated trainees and trainers and analysed the feedback.